Urgency of Establishing Joint Operational Guidelines Between the Police and the National Narcotics Agency to Prevent Duplication of Efforts in Narcotics Investigation - Sudibyo, Andin Wisnu; Suparno, Suparno (Al-Makki Publisher, 2025)
This study aims to analyze the authority of the National Police and the National Narcotics Agency (BNN) to investigate narcotics crimes, as well as the legal implications of the overlapping authority between the two institutions. Using the normative legal method and the statute approach, this study examines the provisions of Law Number 2 of 2002 concerning the Indonesian National Police and Law Number 35 of 2009 concerning Narcotics, as well as other related regulations. A conceptual approach is also applied to explore the legal theory underlying the authority of investigators and the potential for conflict of authority in investigative practices. This study found that overlapping authority can lead to legal uncertainty, human rights violations, and ineffectiveness in the investigation process. Therefore, it is necessary to harmonize regulations, establish joint operational guidelines, and strengthen coordination between the National Police and BNN to prevent conflicts of authority and increase the effectiveness of narcotics law enforcement in Indonesia.